SENI PERTUNJUKAN WAYANG TOPENG GAYA YOGYAKARTA - S., Supriyanto (Greget, 2015)
Wayang Topeng Pedalangan is one of the links in the chain of history of the performing arts in Java and is believed to have been in existence since the 7th century. The art oftopeng Panji, or the Panji masked dance, first emerged after the appearance of the Panji stories inthe middle of the 13th century during the era of the Singasari Dynasty. During the era of theDemak Dynasty, in the 15th century, topeng Panji was developed by a number of religious leaders,including Sunan Kalijaga. The 16th century marked the beginning of the masked dance beingpreserved and developed by traditional puppet masters, or dalang, and their relatives. These dalangpassed on the art of topeng from generation to generation through their network of relatives whoare referred to as Trah Dalang. The role and function of the dalang is connected with the style ofthe performance which is known as Pedalangan style. The influence of the dalang in topengPanji is still evident today in the areas of Yogyakarta, Klaten, Malang, and Cirebon, each of whichis of course adapted to suit its own regional style. Around the middle of the 20th century, the artof topeng pedalangan was revived and reinterpreted by Krida Beksa Wirama to become a classicalversion of topeng in Yogyakarta style. A number of refinements were made to the techniques andform of the dance which adopted the style of classical Yogyakarta dance. Over time, and with thegrowth of various dance groups which performed classical Yogyakarta style dance, such as YayasanSiswa Among Beksa, Mardawa Budaya, Pamulangan Beksa Ngayogyakarta, and Suryokencana,the classical style of masked dance was perfected by the artists of Yogyakarta.Keywords: Topeng, Dalang, Classical.